Modern management concepts and skills - Certo, Samuel C. (Prentice Hall, 2009)
This package contains the following components: MyManagementLab with Pearson eText -- Access Card -- for Modern Management. Modern Management: Concepts and Skills. This text refers to an out of print or unavailable edition of this title.